Water scarcity, intergenerational dynamics and music: the case of the Indigenous community of Chiu-Chiu. Issue 1 (2nd January 2022) - Molina Camacho, Francisco; Park, Susan
ABSTRACT: Water scarcity in northern Chile highlights critical relations between society and nature, marked by conflict and cooperation and mediated by power. Thus, intergenerational dynamics (IGDs) would appear to be a good perspective from which to both reflect and reinforce different approaches to this phenomenon within an Indigenous community when dealing with powerful outsiders. This article assesses the degree to which the Indigenous Community of Chiu-Chiu is internally differentiated according to IGDs, with a focus on the perceived costs and benefits of any outcomes of community negotiations, and how community inequalities regarding water resource outcomes drives the "resistance" to external actors like mining companies. Through IGDs, this article analyzes how the neoliberal market-structured 1981 National Water Code has challenged the development of the Indigenous Community of Chiu-Chiu, and the way the younger generation use music to represent their ancestral claims and fight to enforce the 1993 Indigenous Law and the International Labor Organization 169 Convention on Indigenous and Tribal Peoples.